Working Capital Management and Profitability of Commercial Banks in Nepal (Journal of Management, 2023)
This paper purposes to analyze effects of working capital management on profitability of commercial banks. Empirical data utilized to explores the association between of working capital management and profitability indicators. Based on empirical data, some major financial indicators, credit to deposit ratio, cash reserve ratio, cash and bank balance to total deposits ratio, working capital turnover ratio and liquidity ratios considered as an independent ratio and return on assets, return on equity, and net profit margin as dependent ratios were calculated. Among 20 of the commercial banks of Nepal, only seven commercial banks are taken as sample for the research work. Data were accumulated from secondary data of annual report of model bank and central bank from 2012 to 2022 by the judgmental sampling. Major financial ratios and statistical tools were utilized for the analysis. Descriptive and inferential statistical tools utilized to obtain outcome. In this study, three regression models were tested, and the ROA, ROE, and NPM models were shown to be statistically significant. In the ROA, ROE, and NPM models, respectively, 41%, 52%, and 55% of the sample variation is explained by independent variables.